2018
DOI: 10.1002/chem.201803236
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Co3O4/Ag Nanoparticles Supported on N‐Doped Graphene as Efficient Bifunctional Oxygen Catalysts for Flexible Rechargeable Zinc–Air Batteries

Abstract: Flexible rechargeable zinc–air batteries are considered as one of the most promising power supplies for the emerging flexible and wearable electronic devices. However, the development of flexible zinc–air batteries is stagnant due to the lack of efficient bifunctional catalysts with high oxygen catalytic activity and flexible solid‐state electrolytes with high mechanical stability and ionic conductivity. In this work, Co3O4/Ag@NrGO composite was synthesized by a facile one‐pot method, and the catalyst shows re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 40 publications
(27 reference statements)
1
17
0
Order By: Relevance
“…[31,32] With aview to sustainability and cost, silver has ar obust electrochemical stability in alkaline conditions and ar elatively reasonable price compared to rare-earth elements,i ncluding noble metals.T herefore,e ngineering Co 3 O 4 structure via coupling with conductive Ag particles could be employed as an effective strategy to improve its electrocatalytic performance. [32][33][34][35][36] Obviously,t he formation of metallic Ag is beneficial for the electrical conductivity of Co 3 O 4 . [35][36][37][38] Moreover, recently Zeng et al observed that less than 1% of Ag + cations addition to CoSe 2 could facilitate the charge transfer process that serves as the key step in electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…[31,32] With aview to sustainability and cost, silver has ar obust electrochemical stability in alkaline conditions and ar elatively reasonable price compared to rare-earth elements,i ncluding noble metals.T herefore,e ngineering Co 3 O 4 structure via coupling with conductive Ag particles could be employed as an effective strategy to improve its electrocatalytic performance. [32][33][34][35][36] Obviously,t he formation of metallic Ag is beneficial for the electrical conductivity of Co 3 O 4 . [35][36][37][38] Moreover, recently Zeng et al observed that less than 1% of Ag + cations addition to CoSe 2 could facilitate the charge transfer process that serves as the key step in electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding to the morphology, an appropriate amount of Ag is conducive to improving the OER capability obviously, but excessive Ag might induce aggregation (Figure S3e−f) and impede the catalysis. 49 The peaks between 1.2 and 1.25 V of the CV curves are related to the electrochemical reduction of CoMoO 3 , which has no influence on the OER performance. Moreover, the Tafel slopes were used to analyze the catalytic kinetics in Figure 5b.…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the backward scan CV curves (Figure a), the CoMoO 3 /rGO@Ag-10 catalyst shows an overpotential of 209 mV at 10 mA cm –2 , which is lower than those of pure CoMoO 3 nanoplates (280 mV), CoMoO 3 /rGO@Ag-5 (263 mV), CoMoO 3 /rGO@Ag-20 (237 mV), and commercial RuO 2 (355 mV). Corresponding to the morphology, an appropriate amount of Ag is conducive to improving the OER capability obviously, but excessive Ag might induce aggregation (Figure S3e–f) and impede the catalysis . The peaks between 1.2 and 1.25 V of the CV curves are related to the electrochemical reduction of CoMoO 3 , which has no influence on the OER performance.…”
Section: Resultsmentioning
confidence: 99%
“…The cost of battery materials is closely related to their synthesis process and the price of raw materials. Over the past decades, great efforts have been devoted to developing new eco‐friendly routes to synthesize battery materials and exploring sustainable battery material substitutes …”
Section: Development Trends Of Battery Technologies For Pedsmentioning
confidence: 99%